2002
DOI: 10.1542/peds.110.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Adult Survivors of Pediatric Illness: The Impact on Pediatric Hospitals

Abstract: We describe a subset of adults who have survived diseases of pediatric onset. We focused on the portion of that population that obtains at least some inpatient care at a children's hospital. The data reported here can be used to set a lower boundary for the size of this population, and thereby provide valuable data for health planners as well as clinicians. If one includes estimates of expenses across the continuum of care, the financial impact of this growing population is substantial. Public policy discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 20 publications
1
51
0
2
Order By: Relevance
“…Two papers did not correspond with the definitions of palliative care outlined in table 1, and these were: epidermolysis bullosa61 and paediatric illness (empirical) 26. Both highlighted the importance of having transition programs because of the increasing numbers of young people surviving into adulthood and the role of the family in improving the transition process.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers did not correspond with the definitions of palliative care outlined in table 1, and these were: epidermolysis bullosa61 and paediatric illness (empirical) 26. Both highlighted the importance of having transition programs because of the increasing numbers of young people surviving into adulthood and the role of the family in improving the transition process.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although patients' needs within specific disease categories have been characterized, 4, few investigators have looked at this patient population in aggregate, and the utilization of inpatient treatment facilities by these patients has been poorly described. [31][32][33][34] As efforts to reform health care intensify, an assessment of hospital care for adults with chronic conditions originating in childhood is needed to facilitate the optimal allocation of resources to meet the needs of this population.…”
mentioning
confidence: 99%
“…This finding contrasts with another study in which adult survivors of pediatric illness accounted for 4.9% of all pediatric hospital discharges but accrued 6.3% of total inpatient charges. 9 However, our study population is surgical, and our results may be explained by the fact that pediatric patients undergo highly complex surgical procedures such as the Norwood operation that require an enormous amount of resources to provide adequate care. This is supported by the breakdown of total charges by surgical risk category in Figure 2 that demonstrates higher median total charges for risk category 4ϩ procedures in the pediatric population versus adults.…”
Section: Impact Of Ach Surgery In Pediatric Hospitalsmentioning
confidence: 99%
“…9 As the adult congenital cardiology population progressively grows, the resources required by hospitals to care for this population will increase. We demonstrated that although the number and proportion of congenital heart surgery admissions in pediatric hospitals is increasing, presently these adult admissions do not consume a disproportionate amount of resources among these hospitals.…”
Section: Impact Of Ach Surgery In Pediatric Hospitalsmentioning
confidence: 99%